The Length of Academic Workload and Blood Pressure in Students - I Gusti Ngurah A D Raditya; Mila Citrawati; Melly Kristanti; Diana Agustini P (Jurnal Keperawatan Profesional (KEPO), 2026)
The high prevalence of prehypertension and hypertension in adolescents related to campus activity duration is a concern because long working hours have been associated with increased blood pressure, although previous findings remain inconsistent. This study aimed to determine the correlation between the length of campus-related work and blood pressure in medical students. A cross-sectional design with an analytical survey approach was used. The independent variables were measured using self-administered questionnaires, including the Perceived Stress Scale, Pittsburgh Sleep Quality Index, and Global Physical Activity Questionnaire. Blood pressure was assessed through physical examination using a digital sphygmomanometer. A total of 48 subjects were selected through simple random sampling. Bivariate analysis was conducted using Fisher’s exact test. The results showed that duration of campus activity (p-value = 0.176), stress level (p-value = 0.870), physical activity (p-value = 0.694) and sleep quality (p-value = 0.345), all variables had p-values > 0.05. These findings indicated no significant relationship between the duration of campus activity and blood pressure among medical students at Universitas Pembangunan Nasional “Veteran” Jakarta. Future studies were encouraged to include additional variables such as sodium intake and employ alternative designs such as cohort studies.